Template-free hydrothermal synthesis of ZnO micro/nano-materials and their application in acetone sensing properties. (January 2015) - An, Dongmin; Tong, Xiaoqiang; Liu, Jincheng; Wang, Qiong; Zhou, Qingjun; Dong, Juan; Li, Yan
Highlights: Sheet and rod ZnO micro/nano-materials were synthesized with a template-free hydrothermal method. The morphology of ZnO was depended on the weight ratio of NaOH to zinc salt. The formation mechanism of different morphologies of ZnO products was discussed. The ZnO sensors exhibited a high recovery and fast response to acetone gas. The ZnO sensors exhibited a relative low operating temperature and high sensitivity to acetone gas. Abstract: ZnO micro/nano-materials with sheet and rod morphologies were hydrothermally synthesized with template-free. In synthesis, NaOH was used as the precipitant. The mass ratio of NaOH to zinc salt was the key factor in control the morphology of ZnO product, and synthesized ZnO exhibited a hexagonal wurtzite structure. The gas-sensing properties of the sensors based on the ZnO nanosheets and rods were systematically investigated. At 220 °C, the sensitivity of ZnO nanosheet to 100 ppm acetone was up to 24.9, and the response and recovery times were about 4.9 and 3.1 s, respectively, which was superior to the ZnO rods. The results indicated that ZnO products were potential candidates for acetone sensors, and ZnO nanosheets had a more excellent gas performance than ZnO rods (21.21, 6.0 and 3.2 s). Moreover, the formation and gas-sensing mechanisms of different morphologies of ZnO products were discussed.